Interleukin-6 Level in serm of Iraqi Patients on Maintenance Hemodialysis Therapy - Abdul Wahid, Hind H.; Turki, Kismat M.; AI-Tharb, Asma Y. (Journal of the Faculty of Medicine Baghdad, 2007)
Back ground : Chronic renal failure (CRF) is characterized by progressive destruction of renal mass with irreversible sclerosis and loss of nephrons over a period of at least months to many years which is treated either by dialysis which includes hemodialysis (HD) and peritoneal dialysis (PD) or renal transplantation. Objective : To document the elevation of interleukin-6 (IL-6) in Iraqi HD patients, and to what degree that elevation influences secretion of C-reactive protein (CRP), in addition to its association with other acute phase proteins and kidney function tests . Method : A total of 75 individuals were included in the present study, 50 individuals were treated with HD compared to 25 healthy volunteers. Result : The level of serum IL-6 showed a significant increase in HD patients , and this elevation lead to a high increase in the secretion of CRP as well as the differences in levels of other serum acute phase proteins; ferritin revealed an increase in its level , while alb shows a decrease in its level . Kidney function tests were detected in sera of all the studied groups, which showed an increase in urea and Cr with a decrease in CrCI in patients group.